Institutional and Educational Transformation of Pesantren in Social Capital Perspective: A Phenomenological Study at Pesantren of Miftahul Ulum, Suren, Jember (EDUKASIA, 2021)
This research focused on the development of pesantren, especially in the institutional and educational aspects using a social capital perspective. The pesantren used as a research site is Pesantren of Miftahul Ulum, Suren, Jember. To delve into the focus of this research, the researcher, thus, tried to understand and interpret the development of the pesantren from the perspective of social capital. To achieve these objectives, this research was conducted by using a qualitative approach with the type of phenomenology using a single site design. The data collection technique used was participant observation, so that researcher could participate in every Islamic boarding school's institutional and educational programs. This research finds that social capital is able to transform pesantren from institution with an isolative-traditionalist paradigmatic system to a modernist synthesis. Even the education system is from a dichotomous to a non-dichotomous system (a pattern of education that is oriented towards spiritualistic-humanist values); theocentric to theoanthropocentric pattern. This social capital is also a potential for pesantren as spiritual patrons and the vanguard of the source of values and morality of the surrounding community.